DBU-Catalyzed Inter- and Intramolecular Double Michael Addition of Donor–Acceptor Chromone-Pyrazolone/Benzofuranone Synthons: Access to Spiro-Pyrazolone/Benzofuranone-Hexahydroxanthone Hybrids - Wei, Qi Di; Yao, Yi-Ming; Chang, Shun-Qin; Yang, Wu-De; Tian, Min-Yi; Liu, Xiong-Li; Zhou, Ying (Synthesis, 2020)
A DBU-catalyzed inter- and intramolecular double Michael addition of donor–acceptor chromone-pyrazolone/benzofuranone synthons and 3-methyl-4-nitro-5-alkenylisoxazoles has been established, which constructed structurally diverse spiro-pyrazolone/benzofuranone-hexahydroxanthone hybrids bearing five consecutive stereocenters in good yields (up to 91%) with high diastereoselectivities (up to >20:1 dr). Moreover, this strategy further expanded the synthetic potential of bifunctional donor–acceptor chromones, and demonstrated great potential for applications in medicinal chemistry.
Keywords: donor–acceptor chromone-pyrazolone synthon; donor–acceptor chromone-benzofuranone synthon; inter- and intramolecular double Michael addition; spiro-pyrazolone-hexahydroxanthone hybrids; spiro-benzofuranone-hexahydroxanthone hybrids